Is low back pain asociated with working condition ? (Annals of Medical Research, 2021)
Aim: Low back pain (LBP) is a common musculoskeletal disorder with high lifetime prevalence worldwide. Heavy work and improper sitting conditions during the work hours are among the contributing occupational risk factors. In this study, we aimed to evaluate the incidence and intense of LBP in two different groups working in a hospital setting.Materials and Methods: This is a cross-sectional study that the participants were consisted of 44 porter and 49 desk workers employed full time in a private university hospital at İstanbul. The demographic variables of the participants were evaluated, and they were asked to answer the Oswestry Low Back Pain Disability Questionnaire. Participants are scored on a total score,and the variations between the two groups were evaluated.Results: The mean age of the heavy lifters was 41.32 ± 7.15 years, whereas mean age in desk workers was 33.76 ± 5.19 years. The overall scores did not differ between the groups according to age, gender, smoking status. Total disability score was significantly different between the age and disability groups.Conclusion: The prevalence of LBP is high among hospital employees irrespective of the occupational measures and work load. Orientation of possible occupational risk factors might have a reducing effect on the incidence of LBP and related complications.
Keywords: Hospital employees; low back pain; occupational hazards; occupation related pain